Neurobiological Effects of Chemical Compounds of Species of the Genus Astragalus L. and Prospects for Their Use in Medicine (Review) - M. A. Berezutsky; N. A. Durnova; U. A. Matvienko (Разработка и регистрация лекарственных средств)
Introduction. The genus Astragalus L. is one of the largest genera of flowering plants and includes at least 3,270 species. Individual species of this genus have long been used in traditional and scientific medicine. In recent years, species of the genus Astragalus L. have attracted attention because of the detection of a wide range of neurobiological effects in its representatives. The review presents an analysis of the literature data on experimental and partly clinical studies of various neurobiological effects of extracts and chemical compounds of species of this genus and the prospects for their use in medicine.Text. A variety of neuroprotective effects of these compounds has been established. In many cases, inhibition of oxidative stress, which plays an important role in the development of a number of neurodegenerative diseases, has been noted as a neuroprotective mechanism. Chemical compounds contained in representatives of this genus protect brain neurons from ischemic damage, the effects of neurotoxins and glutamate, and beta-amyloid deposition. These substances have been found to inhibit increased acetylcholinesterase activity and dimyelination processes. These compounds also improve cognitive functions, including memory and learning. Their anticonvulsant effect has been established. Of particular interest is the data indicating the possibility of using some chemical compounds contained in representatives of the genus Astragalus L. in therapy of mental diseases, particularly schizophrenia.Conclusion. The analysis of experimental works for the last ten years shows that extracts and chemical compounds of species of the genus Astragalus L. have a very heterogeneous spectrum of neurobiological action and, probably, may find application in the future as therapeutic agents in neurological and psychiatric practice. Unfortunately, in contrast to a large number of preclinical experiments, clinical trials of these compounds are sporadic. It is also noteworthy that less than one percent of the species of this genus have been investigated to date with respect to neurobiological activity. Thus, more extensive research, clinical trials, studies to standardize and establish therapeutic doses for humans of extracts and chemical compounds of species of the genus Astragalus L. are needed.